An in vitro study on comparative evaluation of shear bond strength of bioactive composite to tooth structure with various dentin conditioning agents - Priyanka Pokkula; Shaik Mohammed Asif; Abdullah Alqarni; Shahabe Saquib Abullais; Shaik Mohamed Shamsudeen; Syed M Yassin; Abosofyan S. Atta; Wahaj Ahmad Khan (AIP Advances)
Bioactive materials are an alternative to conventional restorative materials, which have been promising and challenging at the present time. Etchants or bonding agents are not required as this bioactive material chemically binds to teeth. A potent resin hydroxyapatite complex is formed due to ionic interaction, further preventing microleakage. Applying citric acid and maleic acid is an added advantage in removing the formed smear layer during cavity preparation. This study uses various bonding and conditioning agents to evaluate the strength of bioactive composite shear bonds to the tooth structure. Sixty extracted human maxillary premolars were collected for this study. They were randomly divided into four groups. They were treated with their respective conditioning and bonding agents. The Statistical Package for Social Science software version 23 by IBM was used for data processing and analysis. All p-values less than 0.05 were considered statistically significant. The highest mean bond strength was recorded for the self-etch adhesive group (27.54 MPa), followed by the phosphoric acid group (23.77 MPa), maleic acid group (23.11 MPa), and control group (19.21 MPa). A comparison of intergroup mean bond strength was made using one-way ANOVA. 52.36 was the sum of squares between groups, and that within the group was 19.984, with a degree of freedom between groups being 3 and that within the group being 56, which was statistically significant. The post hoc Tukey test was used for individual group interaction, which was statistically significant. The bond strength of the Activa-restorative material was increased by the pre-conditioning tooth surface. G-bond self-etch adhesive showed the highest efficacy in improving the bond strength among other agents.